Conservative treatment of TB Spondylitis in Dorsolumbar and Lumbar spine - Pradhan, Rabindra Lal; Pandey, Bimal Kumar; Sharma, Sashmit; Lakhey, Shishir; Manadhar, Rajiv Raj; Rijal, Kiran Prasad; Prasai, Tanup (Nepal Orthopaedic Association Journal, 2014)
Introduction: Tuberculosis (TB) is endemic in South Asia including Nepal. TB spine is the most common musculoskeletal manifestations and can have devastating complications. Early diagnosis by proper history, physical and radiological examination is mandatory. Chemotherapy is effective in most cases while some require surgical treatment. Methods: Forty-four patients with clinico-radiological evidence of TB were treated with four drug regime for 18 months and all patients were followed up till the end of the chemotherapy. Results: All 44 patients (M-28/ F-16) had back pain not responding to analgesics and physiotherapy while few had constitutional symptoms. Localized tenderness and paravertebral muscle spasm was present in 32/44 (72.7%) and the rest had palpable swelling at the dorsolumbar and lumbar regions. According to the classification by Oguz et al. the majority of the patients were in the Type I B. Six patients who did not show any improvement in pain and resolution of swelling were admitted and two more drugs (Steptomycin and Ofloxacin) were added. Conclusions: Conservative treatment of TB spondylitis of the lumbar spine can be treated with chemotherapy and appropriate investigations should be performed in patients with back pain who do not respond to rest, analgesics and physiotherapy. DOI: http://dx.doi.org/10.3126/noaj.v3i2.9526 NOAJ July-December 2013, Vol 3, Issue 2, 33-37